Saffron Suffrage: Buddhist Monks and Constitutional Politics in Cambodia - Lawrence, Benjamin (Journal of law and religion, 2022)
As one of the world's only constitutions to recognize Theravada Buddhism as the state religion yet not include a religious exemption to the universal franchise for its monastic community, Cambodia's Constitution stands out as an anomaly. This article traces the ways in which the realities of this remarkably inorganic approach to religion - enshrined in Cambodia's Constitution in 1993, pursuant to a heavily internationalized peace process - have subsequently been shaped by debates occurring within Cambodia's Buddhist institutions, rather than judicial ones. Drawing on data derived from archival research and a series of ethnographic interviews conducted during 2017 and 2018, I home in on decades-old debates about the voting rights of Cambodian monks to show how individual monks justify their participation in electoral politics through a mixture of both secular and religious arguments. The on-the-ground reality of the extension of the franchise to the Buddhist clergy in Cambodia, in other words, is ultimately shaped by an ongoing contestation within the sangha, with proponents and opponents of a religious exception grounding their arguments simultaneously in constitutional and theological vocabularies. The article sheds light on a singular constitutional arrangement - a unique relationship between religious and state institutions that has so far received relatively little scholarly attention - and highlights an instance of constitutional practice that occurs beyond the reach of both judicial and other state institutions.